1993
DOI: 10.1128/aac.37.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal effects of glucose oxidase and peroxidase or their protein conjugates on human immunodeficiency virus type 1

Abstract: Glucose oxidase and peroxidase (lactoperoxidase or myeloperoxidase) are virucidal to human immunodeficiency virus type 1 (HIV-1) in the presence of sodium iodide, as assessed by the loss of viral replication in a syncytium-forming assay or by the inhibition of cytopathic effects on infected cells. In the presence of low concentrations of sodium iodide, five HlV-1 isolates were equally susceptible to this virucidal system at enzyme concentrations of a few milliunits. The loss ofviral replication was linearly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…We previously showed that cell-free HIV-1 is sensitive to inactivation by the peroxidase-H202-halide system (25). An H202 source was found to be essential to inactivate cell-free HIV (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that cell-free HIV-1 is sensitive to inactivation by the peroxidase-H202-halide system (25). An H202 source was found to be essential to inactivate cell-free HIV (15).…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier assay (25), 0.07 U of peroxidase was equivalent to 1 U of peroxidase in the present assay. There was no loss of MPO activity after incubation for 3 days at 37°C in RPMI 1640-FCS; 90.3% of the starting LPO activity remained after 6 days.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Milk lysozyme is active against a number of gram-positive and gram-negative bacteria, which are completely resistant to egg white lysozyme. (27) The presence of lactoferrin enhances the antibacterial activity of lysozyme against E. coli, (18) which also supports the hypothesis that lactoferrin damages the outer membrane of gram-negative bacteria. Several genes encoding lysozymes (28,29) have been found in cow, and the purified lysozymes from cow kidney and stomach are different from cow's milk lysozyme.…”
Section: Introductionmentioning
confidence: 73%
“…Colostrum is rich in antimicrobial components such as lactoferrin, lysozyme, lactoperoxidase, and immunoglobulins. Lactoferrin exhibits antagonistic properties against activities against various bacteria and Candida albicans, (18,21,22) and the interaction of lactoferrin with the cell surface is necessary for antimicrobial activity. These results suggest that lactoferrin exerts its antimicrobial activity by modifying bacterial cell membranes.…”
Section: Introductionmentioning
confidence: 99%